Sistem Kontrol Suhu dan Kelembapan Udara Pada Kumbung Jamur Tiram Berbasis Mikrokontroler Arduino Uno - Sumarsono, Joko; Widhiantari, Ida Ayu; Fadly, M. Yanuar (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 10 No 1 (2025), 2025)
Oyster mushrooms can grow well in areas with low temperatures and damp conditions. Oyster mushrooms can grow optimally in environmental conditions with a temperature range of 16 – 30°C and humidity of 80 – 95%. Mushroom farmers carry out maintenance inside the kumbung manually, namely by manually watering the walls of the mushroom kumbung from the top of the kumbung slowly to create ideal temperature conditions in the kumbung room for fungal growth. This activity is carried out periodically to keep the temperature and humidity in the kumbung room low. The manual system used to maintain mushroom cultivation consumes a lot of time and energy to periodically monitor the temperature and humidity conditions in the storage room, so it is less effective and efficient. Steps to control the condition of the oyster mushroom mushroom room are very necessary in order to obtain conditions in the mushroom room that are always maintained in ideal mushroom growth conditions, so that mushroom growth can be optimal. One technique for controlling the condition of oyster mushroom mushrooms is by using an automatic control system based on a microcontroller. The aim of this research is to apply a temperature and humidity control system to oyster mushroom mushrooms based on an Arduino Uno microcontroller to optimize the growth of oyster mushrooms. From the design results, it is obtained that the temperature and humidity of the air in the mushroom house correspond to the setting point, namely the temperature is not more than 30?C and the air humidity is not less than 80%, where these conditions are suitable for the growth of oyster mushrooms.